Recombination sources in p-type high performance multicrystalline silicon. (7th July 2017) - Sio, Hang Cheong; Phang, Sieu Pheng; Zheng, Peiting; Wang, Quanzhi; Chen, Wei; Jin, Hao; Macdonald, Daniel
Abstract: This paper presents a comprehensive assessment of the electronic properties of an industrially grown p-type high performance multicrystalline silicon ingot. Wafers from different positions of the ingot are analysed in terms of their material quality before and after phosphorus diffusion and hydrogenation, as well as their final cell performance. In addition to lifetime measurements, we apply a recently developed technique for imaging the recombination velocity of structural defects. Our results show that phosphorus gettering benefits the intra-grain regions but also activates the grain boundaries, resulting in a reduction in the average lifetimes. Hydrogenation can significantly improve the overall lifetimes, predominantly due to its ability to passivate grain boundaries. Dislocation clusters remain strongly recombination active after all processes. It is found that the final cell efficiency coincides with the varying material quality along the ingot. Wafers toward the ingot top are more influenced by carrier recombination at dislocation clusters, whereas wafers near the bottom are more affected by a combination of their lower intra-grain lifetimes and a greater density of recombination active grain boundaries.